Guest

sqrt4i - sqrt-4i is equal to (i= iota)

sqrt4i - sqrt-4i is equal to (i= iota)

Grade:11

1 Answers

vikas askiitian expert
509 Points
11 years ago

sqrt4i - sqrt-4i=sqrt4.(sqrti) - sqrt4.(sqrt-i)

                    =2sqrti - 2 (sqrt-1)(sqrti)

                    =2sqrti(1-i)                                  (  sqrt-1 =i )  

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free